Subversive practices of the female body: the monstrous in Ana Mendieta and the subversive in Mary Oliver (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
This article proposes the contemplation of certain subversive practices from the female body, not as better or primitive, nor to declare them as immanent to women, but to allow an exploration from the game, the satire, the monstrous forms of performance in art and the insurgent in poetry, that skim the assigned roles, the univocal sexes and the strategies posed from a heterosexual logic. The forms declare themselves as monstrous because they discolor and disturb, using the root sense that is “to show”; and insurgent because it escapes its univocal destiny, the reason of being of words, its function. This pair of indisciplines devoted to the smallest and the unaffordable, ask about the smaller existences, those that seem not to matter to a system of Power that diminishes the tiny powers and their impotences, their power to do not; it is from these that the female body is questioned and puts itself at risk, it is placed in a state of indeterminacy, which allows it to rethink the purposes and limits that have been imposed on it.
Keywords: Subversion; female body; art; performance; poetry